Flavonoid Ameliorates Anxiety in High Fat High Fructose diet Induced Insulin Resistance in Rats - Das, Prodeep; Nanjundan, Prem Kumar; Nagaraja, Sreeharsha; Meravanige, Girish (Indian Journal of Pharmaceutical Education and Research)
Objectives: Literature review revealed that intake of high fat diet had a likelihood of causing metabolic syndrome and might be involved in causing anxiogenic symptoms. The current study was drafted to appraise hesperidin effect (bioflavonoid) in delaying the progression of anxiety-like symptoms caused by intake of High-Fat High-Fructose Diet (HFHFrD) in male albino Wistar rats. Materials and Methods: Rats were fed with HFHFrD for the induction of insulin resistance (Metabolic syndrome). The role of hesperidin (25 mg/kg p.o), metformin (100 mg/kg p.o) and exercise was assessed in insulin resistance mediated behavioural changes (anxiety). Behavioural parameters, lipid profile of brain/serum, antioxidant status and inflammatory cytokines were determined. Results: We observed elevated weight in body and brain in response to high-fat high-fructose diet and causing anxiogenic-like symptoms. Brain oxidative stress was confirmed by increased lipid peroxidation and neuroinflammation, as well as decline in brain antioxidant profile (SOD, CAT and GSH). Changes in neurobehavior and biochemical parameters significantly postponed the symptoms of anxiety due to prior treatment with hesperidin and metformin. Modest improvement with exercise. Conclusion: Hesperidin can be a potential therapy in the prevention of anxiety like disorders and can mitigate neuroinflammation and prevent it from neurodegeneration, behavioural changes and biochemical alteration linked with insulin resistance.
Keywords: Insulin Resistance; Neuroinflammation; Anxiety; Metformin; Hesperidin and Exercise